2003
DOI: 10.3171/jns.2003.98.5.1040
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of staphylococcal ventriculitis associated with external cerebrospinal fluid drains: a prospective randomized trial of intravenous compared with intraventricular vancomycin therapy

Abstract: Intraventricular vancomycin application is a safe and efficacious treatment modality in drain-associated ventriculitis, with much higher vancomycin levels being achieved in the ventricular CSF than by intravenous administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
72
1
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(84 citation statements)
references
References 26 publications
2
72
1
8
Order By: Relevance
“…In some cases, several attempts are necessary in order to establish a functioning, uninfected shunt, and in such cases, there is evidence of poorer outcome. Intravenous administration of most of the common antimicrobials does not reliably lead to therapeutic antibiotic levels in the CSF (1,19,23,24). Intraventricular antibiotic administration involves a risk of introduction of infection, and administration of some antibiotics by this route is not possible due to neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, several attempts are necessary in order to establish a functioning, uninfected shunt, and in such cases, there is evidence of poorer outcome. Intravenous administration of most of the common antimicrobials does not reliably lead to therapeutic antibiotic levels in the CSF (1,19,23,24). Intraventricular antibiotic administration involves a risk of introduction of infection, and administration of some antibiotics by this route is not possible due to neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Elimination halflives appear to be longer after injection into the lumbar than into the ventricular CSF: the CSF elimination half-life of a hydrophilic radioactive compound ( 111 indium-diethylene triamine pentaacetic acid [ 111 In-DTPA]) injected into the lumbar CSF space was estimated to be 12.4 to 131.1 h (median, 31.7 h) (167). Conversely, the elimination half-life of the large hydrophilic drug vancomycin after intraventricular injection ranged from 3.0 to 20.5 h (median, 5.2 h) (191,192,204).…”
Section: Physiology Of the Exchange Of Drugs Between Blood And The DImentioning
confidence: 99%
“…Our study also confirms the relative delay in CSF linezolid peak concentrations (240 min versus 60 min for plasma after bolus infusion), which is in agreement with the amphiphilic properties of the substance (6). In addition, recent studies demonstrated that tissue penetration of antimicrobial agents is markedly determined by the presence of local or systemic inflammation (12,19). Therefore, the severity of inflammation of the ventricular ependyma could influence the penetration of linezolid into the CSF.…”
mentioning
confidence: 99%
“…However, EVDs are not without complications, the most significant of which is infection resulting in ventriculitis or ventriculomeningitis (2,4,14) caused predominantly by gram-positive bacteria, especially multiresistant coagulase-negative staphylococci (CoNS) and methicillin-resistant Staphylococcus aureus (MRSA) (7). Standard antimicrobial therapy with vancomycin has major limitations: the penetration of vancomycin in the cerebral spinal fluid (CSF), even through inflamed meninges and ventricular ependyma, is poor (1,19). Adverse effects, mainly its nephrotoxicity, often represent contraindications for vancomycin therapy in critically ill patients.…”
mentioning
confidence: 99%